PENGARUH KARAKTERISTIK PEKERJAAN, KEADILAN INTERAKSIONAL DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PT. BANK RAKYAT INDONESIA CABANG PURWOKERTO - Haris Januar; Kundaru Hadiyanto; Heri Setiawan (Majalah Imiah Manajemen & Bisnis, 2020)
This research entitled "The Effect of Job Characteristics, Interactional Justice and Organizational Commitment on Job Satisfaction of PT. Bank Rakyat Indonesia Purwokerto Branch ". The purpose of this study was to analyze and test the significance of the influence of job characteristics on job satisfaction of employees of PT. Bank Rakyat Indonesia Purwokerto Branch, to analyze and test the significance of the effect of interactional justice on job satisfaction of PT. Bank Rakyat Indonesia Purwokerto Branch and to analyze and test the significance of the influence of organizational commitment on job satisfaction of employees of PT. Bank Rakyat Indonesia Purwokerto Branch. The analysis uses multiple linear regression. From this research it can be concluded: The first hypothesis that states job characteristics has a significant effect on job satisfaction of employees of PT. Bank Rakyat Indonesia Purwokerto Branch, with a trust rate of 95%, accepted. This is evidenced by the t test, t calculates the job characteristics greater than t table (4.484> 2.0106). The second hypothesis which states interactional justice has a significant effect on job satisfaction of employees of PT. Bank Rakyat Indonesia Purwokerto Branch, with a trust rate of 95%, accepted. This is evidenced by the t test, t the interactional justice count is greater than t table (2.905> 2.0106). The third hypothesis that states organizational commitment has a significant effect on job satisfaction of employees of PT. Bank Rakyat Indonesia Purwokerto Branch. This is evidenced by the t test, t calculates the organizational commitment greater than t table (3.479> 2.0106).